Nonseparated manifolds and completely unstable flows - Sudhir K. Goel (International Journal of Mathematics and Mathematical Sciences)
We define an order structure on a nonseparated n-manifold. Here, a nonseparated manifold denotes any topological space that is locally Euclidean and has a countable basis; the usual Hausdorff separation property is not required. Our result is that an ordered nonseparated n-manifold X can be realized as an ordered orbit space of a completely unstable continuous flow ϕ on a Hausdorff (n+1)-manifold E.